Findings from the 2022 Yearbook Section on Health Information Exchange - Bloomrosen, Meryl; Berner, Eta S. (Yearbook of Medical Informatics, 2022)
Objectives: To summarize the recent literature and research and present a selection of the best papers published in 2021 related to health information exchange (HIE).Methods: A systematic review of the literature was performed by the two section editors with the help of a medical librarian. We searched bibliographic databases for HIE-related papers using both MeSH headings and keywords in titles and abstracts. A shortlist of candidate 15 best papers was first selected by section editors before being peer-reviewed by independent external reviewers.Results: Major themes of the set of 15 articles included the issues to be addressed in building and maintaining HIEs, HIE implementation barriers and facilitators, and the outcomes of using HIEs. The outcomes of using HIE encompassed the impact on patient care and the ability of HIEs to provide a repository of data for further research.Conclusions: The growth of HIE has followed a course very similar to the growth of electronic health records (EHRs). Initial foci of research included technical issues in the deployment, followed by research on barriers to use. Now that EHRs are more widely implemented and used, the newer research involves the use of the electronic data contained in them. Although HIEs are currently at an earlier stage of maturity and development than EHRs and most of the articles in this review focused on implementation barriers, we have seen the beginning of research on the large amount of longitudinal and diverse data that HIEs can make available. As the implementation and use of HIEs continue to increase and become more widely deployed, we can expect that research about HIE and leveraging HIEs and the data they collect, will continue to increase.
Keywords: Health information exchange, health information; interoperability; data sharing; health information technology; electronic health records; telemedicine